AFIKSASI BAHASA BALI SUATU KAJIAN MORFOFONEMIK - Mahardika, I Putu Permana; Putra, Dwi Mahendra; Dwijayanthi, Ni Made Ari; Paramitha, Ni Made Ayu Susanthi Pradnya; Sentana, Gek Diah Desi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
This study aims to describe the morphophonemic process that occurs as a result of the affixing process. The theory used in this research is the theory of Generative Morphology and Phonology (Schane, 1992). The results of this study indicate; (1) there is a change in sound that produces a new sound due to the meeting of two different morphemes, such as: nasal /Å‹/ becomes a homogeneous sound with preexisting obstruent sounds, such as [p, b, d, t, c , j, s, k, g] and changes in vowel sounds in the affixation process, such as changes in vowels [a, u] turning into vowels [o], [a, i] turning into vowels [e]; (2) there are additional sounds caused by the meeting of two different morphemes, such as the addition of sounds [n, y, w, l, k, t].